The study of unethical behavior affects employee performances in University Malaysia, Terengganu / Iznie Natasya Azmi - Azmi, Iznie Natasya (2015)
The purpose of this study was to investigate the relationship between Unethical Behaviour and Employee Performances. Unethical Behaviour was independent variables in this study and Employee Performances was a dependent variables. The Unethical Behaviour comprised four dimensions which were workplace bullying, employee theft, absenteeism and whistle blowing. The respondent involved in this study was non-academic employees in University Malaysia Terengganu, Gong Badak, Terengganu. The researcher had chosen I0 faculties in University Malaysia Terengganu, Gong Badak, Terengganu. The population of this study was 168 and sample size was 113.